Literatura gatunkowa w internecie, czyli między informowaniem a budowaniem wspólnoty fanów. Na przykładzie portali kryminalnych - Darska, Bernadetta (Postscriptum Polonistyczne, 2020)
The article describes different forms of promoting the literature of genres and the consequences of such promotions for the fans of certain genres. The author examines a crime story portal: ways of describing the genre, offering (or not) the reader the possibility to create some content and cocreate the portal (which can be done by encouraging the readers to make commentaries or participate in the contests). Establishing a direct contact with readers, results in creating a community of fans. The article presents the following websites: „Portal Kryminalny”, „Zbrodnia w Bibliotece”, „Deckare.pl”, „Klub MORD – Klub Miłośników Powieści Milicyjnej” i „Zbrodnicze Siostrzyczki”.